eVtols : smart air mobility project / Muhammad Faiz Abu Hassan - Abu Hassan, Muhammad Faiz (College of Creative Arts, Universiti Teknologi MARA, Kedah, 2024)
The Smart Ocean Mobility Project represents a groundbreaking initiative at the intersection of cutting-edge patrol boat technology and aerial surveillance, driven by artificial intelligence (AI) algorithms. With a strategic focus on transforming maritime security, this project integrates autonomous patrol boats equipped with advanced sensors, communication systems, and autonomous navigation features. Complementing these capabilities are aerial surveillance assets, including drones and autonomous aerial vehicles, extending the reach and efficacy of maritime operations. The project's innovation lies in the seamless coordination between patrol boats and aerial vehicles, fostering a dynamic and responsive maritime security framework. AI algorithms govern adaptive decision-making, enabling real-time responses to evolving threats and emergencies. To facilitate this transformative initiative, the development of specialized infrastructure for the docking, maintenance, and charging of patrol boats and aerial vehicles is paramount. Collaborations with maritime authorities and regulatory bodies play a pivotal role in establishing safety protocols, ensuring the harmonious integration of these advanced technologies into existing maritime security frameworks. Envisioning a future where the synergy between patrol boat technology and smart ocean mobility sets a new standard, the project aspires to redefine maritime security, ushering in an era of comprehensive, efficient, and adaptive solutions for safeguarding oceanic environments.